2011
DOI: 10.1242/jeb.063719
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterisation of apical Na+ and Cl– transport mechanisms of the anal papillae in the larval mosquitoAedes aegypti

Abstract: SUMMARYThe anal papillae of freshwater mosquito larvae are important sites of NaCl uptake, thereby acting to offset the dilution of the hemolymph by the dilute habitat. The ion-transport mechanisms in the anal papillae are not well understood. In this study, the scanning ion-selective electrode technique (SIET) was utilized to measure ion fluxes at the anal papillae, and pharmacological inhibitors of ion transport were utilized to identify ion-transport mechanisms. Na + uptake by the anal papillae was inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…This acidification of the hemolymph was shown to occur in A. aegypti larvae that were transferred to relatively high salt levels (Donini et al, 2007). Evidence that Na + uptake is associated with H + secretion in A. aegypti has been presented (Patrick et al, 2002b;Stobbart, 1967) and we have shown that Na + uptake at the papillae is likely to occur through a putative Na + channel driven by the electrical gradient established by the apical VA, which secretes H + into the water (Del Duca et al, 2011). We have since shown the expression of NHE3 on the apical side of the anal papilla epithelium and cannot rule out the possibility of Na + uptake coupled to H + secretion via this transporter (Chasiotis et al, 2016).…”
Section: Nacl Rearingsupporting
confidence: 51%
“…This acidification of the hemolymph was shown to occur in A. aegypti larvae that were transferred to relatively high salt levels (Donini et al, 2007). Evidence that Na + uptake is associated with H + secretion in A. aegypti has been presented (Patrick et al, 2002b;Stobbart, 1967) and we have shown that Na + uptake at the papillae is likely to occur through a putative Na + channel driven by the electrical gradient established by the apical VA, which secretes H + into the water (Del Duca et al, 2011). We have since shown the expression of NHE3 on the apical side of the anal papilla epithelium and cannot rule out the possibility of Na + uptake coupled to H + secretion via this transporter (Chasiotis et al, 2016).…”
Section: Nacl Rearingsupporting
confidence: 51%
“…In larval Ae . aegypti , four anal gills surrounding the anal opening serve as the major sites for Na + , Cl − and K + uptake by H + -ATPase and Na + /K + -ATPase 37,69,70 . The osmotic uptake of water at the anal gills is the primary external site of ion uptake, normally contributing to 33% of the body weight gain per day 70 .…”
Section: Discussionmentioning
confidence: 99%
“…The anal gills of mosquito larvae are important primary sites of NaCl uptake, thereby acting to offset the dilution of the hemolymph by the dilute habitat [21] , [43] , [44] . Donini and O'Donnell [22] confirmed with the use of self-referencing ion-selective microelectrodes that the anal gills of Ae.…”
Section: Discussionmentioning
confidence: 99%